2016
DOI: 10.20944/preprints201610.0021.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zinc Finger and X-Linked Factor (ZFX) Binds to Human SET Transcript 2 Promoter and Transactivates SET Expression

Abstract: SET protein carries out multiple functions including those for protein phosphatase 2A (PP2A) inhibition, histone modification, DNA repair and gene regulation. SET overexpression has been detected in brain neurons of Alzheimer's disease patients, follicle theca cells of Polycystic Ovary Syndrome (PCOS) patients, and ovarian cancer cells, indicating that SET may play a pathological role for these disorders. SET transcript 2, produced by a specific promoter, represents a major transcript variant in different cell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…that are critical for SET-β transactivation in both HEK293 and HeLa cells. 65 Multiple Sp1 binding sites are found in both SET-α and SET-β promoter regions, but their effects on each isoform transcription are different. In HEK 293, HeLa, AML, HL-60, and HEL cells Sp1 positively contributes to SET-α gene transcription in vivo while Sp1 knockdown leads to reduction in SET-α mRNA level, whereas Sp1 deficiency has no effect on SET-β transcription.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…that are critical for SET-β transactivation in both HEK293 and HeLa cells. 65 Multiple Sp1 binding sites are found in both SET-α and SET-β promoter regions, but their effects on each isoform transcription are different. In HEK 293, HeLa, AML, HL-60, and HEL cells Sp1 positively contributes to SET-α gene transcription in vivo while Sp1 knockdown leads to reduction in SET-α mRNA level, whereas Sp1 deficiency has no effect on SET-β transcription.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…These TFs are usually overexpressed in cancer cells, thereby enhancing the transcription of SET. Siliang et al found that there are 4 zinc finger and X‐linked factor (ZFX) binding sites in the proximal promoter region that are critical for SET‐β transactivation in both HEK293 and HeLa cells . Multiple Sp1 binding sites are found in both SET‐α and SET‐β promoter regions, but their effects on each isoform transcription are different.…”
Section: Transcriptional and Post‐translational Regulation Of Setmentioning
confidence: 99%